A Revertant of the Major Founder Native American HaplogroupC Common in Populations From Northern South America (2006)
ABSTRACT: We examined the mtDNA RFLP diversity of 17 Native American populations from Colombia. Five of the populations studied were found to have variable frequencies of a mtDNA type lacking the characteristic changes of haplogroups A-D. Sequencing of mtDNA HVS-I and II showed that this ‘‘null’’ RFLP type carries all the substitutions characteristic of Native American founder lineage C. A back mutation has therefore recreated theþ13,259HincII/ 13,262AluI restriction sites that typify RFLP haplogroup C. This revertant C lineage is further characterized by three changes in HVS-II sequence: C/T transitions at positions 115 and 152, and the deletion of an A residue at position 116. This lineage is observed at high frequency mostly in populations from Greenberg’s Equatorial–Tucano linguistic family. Genetic structure analyses are consistent with the reversion mutation occurring at an early stage during the tribalization process.